2019
DOI: 10.1177/0883073819893159
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Journey of Patients with Riboflavin Transporter Deficiency Type 2

Abstract: Purpose: To identify symptoms and health care interactions with patients with riboflavin transporter deficiency (RTD) type 2 prior to diagnosis. Methods: Parents of children with riboflavin transporter deficiency type 2 (n = 10) were interviewed to collect data on the patient’s clinical journey. Results: The average diagnostic delay was 27.6 months. Neurologists were the most commonly visited clinician (90%). Common symptoms during the first year of the patient’s clinical journey included abnormal gait and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
(94 reference statements)
0
21
0
Order By: Relevance
“…RTD syndrome, formerly known as Brown-Vialetto-Van Laere (BVVL) syndrome, is a rare autosomal-recessive motor neuron disease. Typical clinical features reported include pontobulbar palsy, limb and axial muscle weakness, sensorineural hearing loss, optic atrophy, ataxia, and respiratory compromise [ 24 , 25 ]. The age of onset is variable, and young patients show different phenotypes with variable prognosis, often influenced by the initiation of RF treatment.…”
Section: Introductionmentioning
confidence: 99%
“…RTD syndrome, formerly known as Brown-Vialetto-Van Laere (BVVL) syndrome, is a rare autosomal-recessive motor neuron disease. Typical clinical features reported include pontobulbar palsy, limb and axial muscle weakness, sensorineural hearing loss, optic atrophy, ataxia, and respiratory compromise [ 24 , 25 ]. The age of onset is variable, and young patients show different phenotypes with variable prognosis, often influenced by the initiation of RF treatment.…”
Section: Introductionmentioning
confidence: 99%
“…While sensorineural hearing loss is the most common initial presentation associated with RTD (Bosch et al, 2012), our patient had the unusual initial features of macrocytic anemia and intermittent neutropenia, subsequently determined to be megaloblastic based on bone marrow findings. After excluding the common etiologies of megaloblastic anemia, including vitamin B12 and folic acid deficiencies, the mechanism underlying the megaloblastic anemia related to RTD2 still remains unclear (Amir et al, 2019). Neutropenia associated with RTD or riboflavin deficiency has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…Age of onset varies from infancy to adulthood and is often precipitated by intercurrent infections (Bosch et al, 2012). Amir et al recently reported megaloblastic anemia in a patient with RTD type 2 (RTD2) with anemia present in other individuals in their 10 patient cohort (Amir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other common clinical features present in RTD2 and RTD3 patients are dysarthria, weakness and hypotonia, whereas the most common differences concern facial weakness which is typical of RTD3 patients and vision loss, characteristic of RTD2 patients [ 103 , 104 ]. RTDs are sometimes responsive to high doses of Rf treatment and characterized by biochemical abnormalities in the acylcarnitine profiles, thus resembling another inborn error of metabolism mainly affecting muscle, named MADD (Multiple Acyl-CoA Dehydrogenase Deficiency) we will discuss later on [ 105 ].…”
Section: Remaining Challenges In Neuronal and Muscular Flavin Homementioning
confidence: 99%